2004
DOI: 10.1103/physrevd.69.016002
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative Faddeev-Popov formula and the infrared limit of QCD

Abstract: We show that an exact nonperturbative quantization of continuum gauge theory is provided by the Faddeev-Popov formula in the Landau gauge, ␦(‫•ץ‬A)det͓Ϫ‫•ץ‬D(A)͔exp͓ϪS YM (A)͔, restricted to the region where the Faddeev-Popov operator is positive Ϫ‫•ץ‬D(A)Ͼ0 ͑Gribov region͒. Although there are Gribov copies inside this region, they have no influence on expectation values. The starting point of the derivation is stochastic quantization which determines the Euclidean probability distribution P(A) by a method tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
302
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(343 citation statements)
references
References 72 publications
(101 reference statements)
40
302
1
Order By: Relevance
“…The arguments for the Gribov-Zwanziger framework to achieve this further restriction to the absolute minima in lattice formulations [30], furthermore involve the thermodynamic or infinite-volume limit, in which the common boundary of the fundamental modular region and the first Gribov region dominate the minimal Landau-gauge configuration space [31]. To find absolute minima in lattice simulations is not feasible for large lattices as this is a nonpolynomially hard computational problem.…”
Section: Discussionmentioning
confidence: 99%
“…The arguments for the Gribov-Zwanziger framework to achieve this further restriction to the absolute minima in lattice formulations [30], furthermore involve the thermodynamic or infinite-volume limit, in which the common boundary of the fundamental modular region and the first Gribov region dominate the minimal Landau-gauge configuration space [31]. To find absolute minima in lattice simulations is not feasible for large lattices as this is a nonpolynomially hard computational problem.…”
Section: Discussionmentioning
confidence: 99%
“…First of all this concerns the interrelation of functional methods like the general flows studied here, Dyson-Schwinger equations [149][150][151][152][153][154][155][156][157], stochastic quantisation [158][159][160], and the use of N PI effective actions [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177]. All these methods have met impressive success in the last decade, in particular if it comes to physics where a perturbative treatment inherently fails.…”
Section: Applications To Functional Methodsmentioning
confidence: 99%
“…They have been successfully used for the description of the infrared sector of QCD formulated in Landau gauge, initiated in [149,150], for a review see [151]. This approach is also tightly linked to a similar analysis in stochastic quantisation [158][159][160].…”
Section: Dses As Integrated Flowsmentioning
confidence: 99%
“…Zwanziger [3] has suggested that the behaviour of both propagators in Landau gauge results from the restriction of the gauge fields to the Gribov region, where the Faddeev-Popov operator is nonnegative. Generically, one gauge orbit has more than one intersection (Gribov copies) within the Gribov region.…”
mentioning
confidence: 99%
“…In particular the infrared behaviour of the ghost propagator in the Landau gauge is related to the so-called Kugo-Ojima confinement criterion [1], which expresses the absence of coloured massless asymptotic states from the spectrum of physical states in terms of the ghost propagator at vanishing momentum. On the other hand the suppression of the gluon propagator in the infrared was argued to be related to the gluon confinement [2].Zwanziger [3] has suggested that the behaviour of both propagators in Landau gauge results from the restriction of the gauge fields to the Gribov region, where the Faddeev-Popov operator is nonnegative. Generically, one gauge orbit has more than one intersection (Gribov copies) within the Gribov region.…”
mentioning
confidence: 99%